Analysis of Peti dam swelling process - Tavares de Castro, A. (2012)
Several large concrete dams built during the first half of the 20th century, when the knowledge about the deterioration processes on the concrete was limited, are yet in service, although presenting, in some cases, signs of severe deterioration due to chemical internal reactions. When these structures have significant economic importance and its replacement is not easy or is very expensive, studies carried out in order to understand and characterize the deterioration processes are of utmost importance to extend the life of these structures with adequate safety conditions. In this paper an overall view of the studies performed to a Brazilian arch dam, Peti dam, are presented. This dam, whose construction was finished in 1945, is submitted to a swelling process due to alkali-aggregate reactions (AAR). Since the detection of its abnormal behaviour, in the 60s of the last century, mainly through the observation of the development of significant cracks, several studies had been carried out involving the experimental evaluation of the concrete properties. A monitoring system was implemented in 1997 allowing the analysis and interpretation of the observed structural behaviour of dam. In the last year, CEMIG and LNEC have been cooperating in order to analyse the safety conditions of Peti dam through experimental and numerical studies. This paper presents a methodology to determine the free swelling history in the concrete covering the 66 years life of the dam with base on the environmental conditions. These results will be used as prescribed deformations in a chemo-viscoelastic-damage model in order to predict the long term behaviour of the dam. The characterization of the swelling action was based on the data collected from the monitoring system and on laboratorial tests results.